Evolution of ultraviolet vision in shorebirds (Charadriiformes) - Ödeen, Anders (The Royal Society, 2010)
Diurnal birds belong to one of two classes of colour vision. These are distinguished by the maximum absorbance wavelengths of the SWS1 visual pigment sensitive to violet (VS) and ultraviolet (UVS). Shifts between the classes have been rare events during avian evolution. Gulls (Laridae) are the only shorebirds (Charadriiformes) previously reported to have the UVS type of opsin, but too few species have been sampled to infer that gulls are unique among shorebirds or that Laridae is monomorphic for this trait. We have sequenced the SWS1 opsin gene in a broader sample of species. We confirm that cysteine in the key amino acid position 90, characteristic of the UVS class, has been conserved throughout gull evolution but also that the terns Anous minutus, A. tenuirostris and Gygis alba, and the skimmer Rynchops niger carry this trait. Terns, excluding Anous and Gygis, share the VS conferring serine in position 90 with other shorebirds but it is translated from a codon more similar to that found in UVS shorebirds. The most parsimonious interpretation of these findings, based on a molecular gene tree, is a single VS to UVS shift and a subsequent reversal in one lineage.